2015
DOI: 10.2147/dddt.s75152
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PD-L1 and APE1 is associated with tumorigenesis and poor prognosis of gastric cancer

et al.

Abstract: IntroductionGastric cancer is a fatal malignancy with a rising incidence rate. Effective methods for early diagnosis, monitoring metastasis, and prognosis are currently unavailable for gastric cancer. In this study, we examined the association of programmed death ligand-1 (PD-L1) and apurinic/apyrimidinic endonuclease 1 (APE1) expression with the prognosis of gastric cancer.MethodsThe expressions of PD-L1 and APE1 were detected by immunohistochemistry in 107 cases of human gastric carcinoma. The correlation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 45 publications
2
126
4
1
Order By: Relevance
“…PD-L1 expression has been associated with clinicopathological characteristics and prognosis in different cancers [2124]. We found no significant difference between PD-L1 mRNA expression and gender, age, KPS score, differentiation, the number of metastatic organs, liver metastasis, and peritoneal metastasis ( P > 0.05).…”
Section: Discussionmentioning
confidence: 51%
“…PD-L1 expression has been associated with clinicopathological characteristics and prognosis in different cancers [2124]. We found no significant difference between PD-L1 mRNA expression and gender, age, KPS score, differentiation, the number of metastatic organs, liver metastasis, and peritoneal metastasis ( P > 0.05).…”
Section: Discussionmentioning
confidence: 51%
“…However, for patients with GC, the association between the expression of PD-L1 and their prognosis remains controversial. Multiple studies have indicated that positive PD-L1 expression is associated with a significantly poor OS1617181920212223, but other studies could not confirm this finding2425.…”
Section: Discussionmentioning
confidence: 99%
“…In an unselected GC population, PD-L1 was overexpressed in 42%-50% of patients (52) (53) , and was correlated with poor survival rates (53) . Inhibition of PD-L1…”
Section: Pd-1/pd-l1 Pd-l2 Pathwaymentioning
confidence: 99%